The influence of landmarks and urban form on cognitive maps using virtual reality - Bruns, Conner Ray (Kansas State University, 2018)
Landmarks are universal components of human urbanization. We are a species driven to mark the land with symbolic structures and craft meaning in our built environments. From ancient wonders such as Stonehenge to modern icons like the St. Louis Arch, we have been designing landmarks since the dawn of civilization. Cities, towns, and neighborhoods incorporate landmarks as elements of cultural expression and tools for navigation. Individuals use landmarks as reference points to create an internal cognitive map, permitting more efficient navigation throughout a city and contributing to a heightened sense of place. To aid in research regarding the role of landmarks on cognitive maps and place-identity, we have designed a novel testing paradigm in which subjects wear a virtual reality (VR) head-mounted display (HMD) and traverse a hypothetical urban environment using a gaming controller. The virtual environment (VE) features a gridded street network measuring 5x5 blocks and guides subjects along a fixed route through residential, park, commercial and industrial districts. Along this fixed route, subjects are exposed to ten distinct landmarks. After navigating the VE, subjects are tasked with delineating their perceived route, landmark locations, and district boundaries through map drawing tasks on grid paper as well as a scene recognition task. The most significant finding revealed landmark configuration accuracy to be highly correlated with performance on the route recall and moderately correlated with performance on the scene recognition task. This suggests that, regardless of the landmark type, individuals who more precisely recalled landmark locations also navigated the route and identified scenes more accurately. Landscape and urban planners can leverage these findings to advocate for the strategic inclusion of landmarks throughout an urban fabric, which we term Landmark Configuration Plans (LCP).
Keywords: Landmark; Urban form; Cognitive map; Virtual reality; Place identity; Landmark configuration plan